Laser printing of silver-based micro-wires in ZrO2 substrate for smart implant applications. (November 2020) - Moura, C.G.; Faria, D.; Carvalho, O.; Pereira, R.S.F.; Cerqueira, M.F.; Nascimento, R.M.; Silva, F.S.
Highlights: A hybrid approach for printing micro-wires on zirconia substrate were presented. The resistivity of the micro-wires was assessed by the four-probe method. The mechanical performance of zirconia before and after wire printing was presented. Laser technology was successfully used both to create channel and sinter silver powder inside them. Abstract: Smart implants are endowed with functions of sensing, actuating and control to solve problems that may arise during their use. The assembly of these functions along the implant surface is still a challenge. However, with the advent of 3D printing, it is possible to print on implants' surface, communication channels or micro-antennas or even sensoric/actuating areas. Hence, a positive impact on the long-term performance of the implants (including hip, dental and knee) may be expected with the proposed approach. Despite titanium and Ti6Al4V titanium alloy are the standard choice for implants fabrication, 3Y-TZP (tetragonal 3% mol yttria-stabilized zirconia) has emerged as a ceramic material suitable to overcome titanium alloy problems, due to its numerous advantages. In this sense, this work is concerned with the ability of printing silver-based communication system in zirconia substrates by using laser technology. For this purpose, micro-cavities were created on ZrO2 substrate, where the silver powder was placed and sintered into them. Through the laser approach, silver-based wires with great quality and low resistivity values were achieved. The flexural strength results showed that the mechanical resistance of zirconia disks was affected by laser micro-wire printing, which decreased as the laser passage was performed. Based on the results, it is believed that the proposed approach seems to be effective for the manufacturing of implants with intrinsic capacities, useful for smart implant applications.